LEXICAL ACQUISITION AND LITERARY COMPETENCE. LINGUISTICS AND CULTURAL STUDIES - Dorin CHIRA; Oana Aurelia GENCĂRĂU (Studia Universitatis Babeş-Bolyai. Philologia, 2019)
We include in this volume a series of studies focusing on lexical acquisition - first and foremost - on translation and translatology, the evaluation of linguistic competence, as well as certain well-defined cultural aspects. What brings these papers together, offering this volume its cohesion, is an item to which research returns again and again, almost obsessively. In every study there is a question revolving around the word, its importance in the meaningful developments of humanity, from linguistic acquisition, to language learning—be it the mother tongue or a foreign language—and up to the challenge posed by the process of translation.